Antioxidant and Free Radical Scavenging Capacity of Seed and Shell Essential Oils Extracted from Abrus precatorius (L) - Okoh, Sunday O. (Antioxidants (Basel), 2014)
Essential oils from plants have been proven safe as natural antioxidants, and few are already marketed as digestive enhancers as well as in prevention of several degenerative diseases. This study evaluated the antioxidant capacity of seed and shell essential oils of Abrus precatorius (L), a herb used for ethno-medicinal practices in Nigeria. The essential oils were obtained by hydro-distillation. The ability of the oils to act as hydrogen/electrons donor or scavenger of radicals were determined by in-vitro antioxidant assays using 2,2-diphenyl-2-picryl-hydrazyl free radical (DPPH(.)) scavenging; 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) radical scavenging; lipid peroxide and nitric oxide radicals scavenging assays. The IC(50) of the seed and shell oils (2.10 mg/mL and 1.20 mg/mL respectively) showed that antioxidant activity is higher than that for the standard drugs (3.20 mg/mL and 3.40 mg/mL) for the nitric oxide scavenging assay. The lipid peroxidation radical activity of the oils were similar to vitamin C, weak DPPH and ABTS radical scavenging activities were discovered in comparison to vitamin C and rutin. Generally, in the four antioxidant assays, a significant correlation existed between concentrations of the oils and percentage inhibition of free radicals and lipid peroxidation. The composition of A. precatorius essential oils reported earlier may account for their antioxidant capacity.